Non-Test Assessment Innovation Performance For Maharah Kalam Through Youtube In The Pandemic Era - R. Umi Baroroh; Nafisatun Nisa (Ijaz Arabi Journal of Arabic Learning, 2022)
This study aims to innovate the development of the mahârah kalâm assessment instrument in the pandemic era through youtube media and to analyze the instrument developed using the Rasch model analysis. This research uses the RD (Research and Development) method. The instrument items made were 21 items developed from four characteristics: pronunciation, smoothness, vocabulary, grammar, and understanding, with a total of 31 students. The assessment developed is in the form of a rating scale with 1-4 criteria. Data analysis was carried out by Winstep software. Based on the results of this research from the output of the Winstep program, it can be seen that the instrument made has a good reliability value and can measure students' abilities. This is indicated by the item reliability score of 0.72, the person reliability value of 0.82, the Cronbach alpha value of 0.87, the MNSQ Infit and MNSQ Outfit values , respectively 1.01 and 1.00, the ZSRD infit 0.00 and Outfit ZSTD of -0.01. At the same time, the number of items that fit is 11 items and ten items that are misfits.